Induced breeding of African catfish (Clarias gariepinus) under varying brood stock ratios (Global Journal of Science Frontier Research, 2012)
A reputable fish farm in Abeokuta, Ogun State, Nigeria were used to carry out studies on the induced breeding of Clarias gariepinus under varying brood stock ratios. Six gravid females weighing 1.00 kg each and 6 reproductively matured males weighing 1.00 kg were used for the three induced breeding trials in ratios of 2:1, 1:2 and 2:3, female/male respectively. Females were injected at a dosage of 0.50 ml ovaprim/kg body weight and 0.25 ml/kg body weight for males. Hatching starts after 24 hours of incubation and lasted for 6 hours. Dissolved oxygen, pH, ammonium ion, nitrate ion levels and temperature were monitored. Mean weight of eggs produced is 285.00 g ± 65.00 with a relative percentage weight of eggs to body weight of 26 to 33%. Also, fecundity was the same in all the treatments with a value of 66,000+100 eggs. The lowest pseudo-gonadosomatic index of 41.50+6.50 was recorded in treatment 1, while the highest value of 51.00+3.00 was recorded in treatment 2. The effect of the varying brood stock (female:male) ratios in all the trials were not significantly different at (P
Keywords: Brood stock; Clarias; fertilization; induced breeding